2019
DOI: 10.1088/1742-6596/1272/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Electric impedance and the healing of diabetic foot ulcers

Abstract: Diabetic foot (DF) is a complication of people suffering from diabetes mellitus (DM) with an overall prevalence estimated as 6.3%. Healing of diabetic ulcers takes several weeks, and follow up is needed both to assess the improvement of the wound and to detect possible complications. Ulcer diameter, pH and temperature have been used for such purpose and some authors have also proposed the use of Electric Bioimpedance (EBI). The results presented in this paper are taken from a small pilot study carried out to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Study E3, conducted in patients with pressure ulcer (PU), showed that PA was effective in the evaluation of lesions since it significantly decreased in these patients (17) . In another study (E4), which evaluated PA in foot ulcers, the authors could not demonstrate effectiveness in the use of PA related to the healing process (18) . Although there was healing in the patients, without complications, the EBI parameters did not increase during treatment, as expected.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Study E3, conducted in patients with pressure ulcer (PU), showed that PA was effective in the evaluation of lesions since it significantly decreased in these patients (17) . In another study (E4), which evaluated PA in foot ulcers, the authors could not demonstrate effectiveness in the use of PA related to the healing process (18) . Although there was healing in the patients, without complications, the EBI parameters did not increase during treatment, as expected.…”
Section: Resultsmentioning
confidence: 97%
“…After reading the full texts, 5 studies were included for the qualitative synthesis, as shown in Figure 1. In relation to the outcomes, four evaluated wound healing (E1, E2, E3, E4) (15)(16)(17)(18) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations